Pengaruh Current Ratio (CR) Dan Debt To Assets Ratio (DAR) Terhadap Return On Assets (ROA) Pada PT Matahari Departement Store Tbk Periode 2014-2024 - Bait Dwi Umbi; Bulan Oktrima (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to see the effect of Current Ratio and Debt to Assets Ratio on Return on Assets at PT Matahari Department Store TBK. Period 2014-2024. The research method used in this study is a quantitative approach. Data analysis used are: Descriptive Statistical Test, Normality, Multicollinearity, Heteroscedasticity, Autocorrelation, Multiple Linear Regression, t-test (partial), f-test (simultaneous), Determination Coefficient (R2). The t-test results show that Current Ratio has a significant effect on Return on Assets with t count (2.921) > t table (2.365) and significance of 0.019 < 0.05. Meanwhile, Debt to Assets Ratio does not have a significant effect on Return on Assets with t count (1.328) < t table (2.365) and significance of 0.221 > 0.05. The F-test results show that Current Ratio and Debt to Assets Ratio simultaneously have a significant effect on Return on Assets with F count (4.460) ≈ F table (4.46) and significance of 0.050 = 0.05. The coefficient of determination (Adjusted R²) of 0.409 or 40.9% indicates that both independent variables can explain the variation in Return on Assets by 40.9%, while the remaining 59.1% is influenced by other factors outside this study.